Peran Mahasiswa Kukerta dalam Optimalisasi Pengembangan Potensi Desa di Kepenghuluan Karya Mukti - Bayhakki, Bayhakki; Nizam, Azrul; Dzakwan, Adib; Herryka, Afrialdi; Azriyani, Aulia; Febrioni, Febrioni; Pinem, Pulungen; Paliyoen, Rossa Putri; Salsabila, Salsabila; Andriani, Suci; Novianti, Tina (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Community Service Program (Kuliah Kerja Nyata or KUKERTA) is a community service initiative by students of the University of Riau. The program aims to apply the knowledge and technology gained during their studies to provide tangible benefits to the community. In 2024, KUKERTA was implemented in Kepenghuluan Karya Mukti, Rimba Melintang District, Rokan Hilir Regency, from July 14 to August 23, 2024. This program was designed to drive sustainable development through the improvement of education, economy, health, agriculture, and fisheries sectors. With a participatory approach, KUKERTA students involved the community in various activities such as workshops, socialization, and hands-on practices. The positive impacts were seen in the form of increased agricultural and fisheries productivity, improved literacy awareness, community health, and optimized utilization of local resources. This program not only brought significant changes to Kepenghuluan Karya Mukti but also strengthened the relationship between the university and the community in achieving shared goals for a better future.